Despre paternitatea piesei „Occisio Gregorii in Moldavia Vodae Tragedice Expressa” - Tiberius, Vasiniuc (Theatrical Research, 2020)
About Authorship of the Play "Occisio Gregorii in Moldavia Vodae Tragedice Expressa" In the second half of the 18th century, the beginnings of the Romanian theatre bring to our attention the play "Occisio Gregorii in Moldavia Vodae Tragedice Expressa". With an uncertain authorship, disputed, most often, between Samuil Vulcan and Ion Budai-Deleanu, it largely follows the canons of the Jesuit school theatre. The main scenes, which depict Prince Grigore Ghica’s dethronement and murder by the Tur- ks, are joined by a series of burlesque interludes, with crude humour, with the role of relaxing the serious atmosphere generated by the tragic event. Our study seeks to highlight the different positions of exegesis, both in terms of establishing the author of the play and the genre classification. The study also aims to highlight structures and elements of stylistic and linguistic specificity of the analyzed work.